Managers’ career concerns and firm R&D investments: the case of emerging market firms - Su, Jiaoyue (2024)
Investments in R&D are critical for firms to build competitive advantage and achieve sustained long-term growth. As such, scholars have long interested in understanding the role of CEO characteristics in determining R&D investments. While existing studies have focused on explicit CEO incentives from compensation contracts, there is a lack of understanding of how CEOs’ implicit incentives tied to career concerns influence R&D investment decisions. Also, previous studies emphasize CEOs’ career concerns in the context of US firms. Emerging markets, such as China, have different characteristics in terms of the managerial labor market and institutional environment, resulting in distinct incentives for CEOs, yet research in this area remains scarce. This thesis seeks to address these gaps and advances the literature.